2017
DOI: 10.1007/s11356-017-9182-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of phthalates in aquatic environment and their removal during wastewater treatment processes: a review

Abstract: Phthalates are plasticizers and are concerned environmental endocrine-disrupting compounds. Due to their extensive usage in plastic manufacturing and personal care products as well as the potential to leach out from these products, phthalates have been detected in various aquatic environments including drinking water, groundwater, surface water, and wastewater. The primary source of their environmental occurrence is the discharge of phthalate-laden wastewater and sludge. This review focuses on recent knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 131 publications
3
38
0
Order By: Relevance
“…The DMA results with each of the plasticizers are depicted in Figure and Table . It can be observed that each of the curves have just one peak, suggesting that the plasticizer had good compatibility with PVC and the compounds were homogenous . Glass transition temperature ( T g ) is an important metric of plasticizing efficiency; it can be determined as the temperature at the maximum of the tan δ curve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DMA results with each of the plasticizers are depicted in Figure and Table . It can be observed that each of the curves have just one peak, suggesting that the plasticizer had good compatibility with PVC and the compounds were homogenous . Glass transition temperature ( T g ) is an important metric of plasticizing efficiency; it can be determined as the temperature at the maximum of the tan δ curve.…”
Section: Resultsmentioning
confidence: 99%
“…Phthalate use in children's toys, food packaging, and medical devices, among others, has been restricted in many countries . However, given the current petroleum shortages, increasing numbers of researchers have focused on plasticizers from renewable materials …”
Section: Introductionmentioning
confidence: 99%
“…2013 ; Winkel et al. 2011 ), phthalates [phthalic acid esters (PAEs)]; Gani et al. 2017 ; Jiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalates, or phthalic acid esters, are utilized as plasticizers and solvents. Similar to BPA, the use of phthalates in numerous products results in widespread human exposure (Wormuth et al 2006), and various phthalates are ubiquitously present in the environment (Gani, Tyagi, and Kazmi 2017). Phthalates have been suggested to contribute to male reproductive disorders, including testicular dysgenesis syndrome which may have fetal origin (Bornehag et al 2015;Dorman et al 2018;Habert et al 2009;Radke et al 2018;Skakkebaek, Rajpert-De Meyts, and Main 2001;Swan et al 2015).…”
Section: Introductionmentioning
confidence: 99%